Overcoming barriers to cervical cancer screening in a developing country like Pakistan - Zafar, Ramsha; Asma Burney (Journal of the Pakistan Medical Association, 2022)
Cervical cancer is the second most prevalent cancer in Pakistani women of the reproductive age group (15-44 years), while in women of all ages, it ranks as the third most common. It is estimated that around 20 women are found to have cervical cancer per day, ranking Pakistan in the top 10 countries with the highest cancer-related mortality rates. [1] In 2020 alone, cervical cancer took the lives of 341, 831 women, 90% of whom belonged to developing countries including Pakistan. In the same year, it affected 604, 127 women, from which only 12% were from regions like the North America and Europe, while the remaining belonged to the developing world. [2] This startling disparity can be attributed to the introduction of pap smears in the developing world, like the United States and the United Kingdom, which saw >70% decline in cervical cancer mortality since screening through Pap smears was initiated in these countries. [3]. In Pakistan, several studies have shown that women of the reproductive age group lack basic awareness regarding cervical cancer and screening via Pap smears. A survey on 873 women between 18-28 years found 70.1% of the participants were completely unaware of cancer. [4] A more extensive study consisting of 1070 women between ages 21-30 years found that only 2.2% of their study’s population was able to identify the symptoms and risk factors for cervical cancer, while Pap smear was recognized as a screening test by only 2.5% of the same. The Pap smear uptake in this population was 2%. [5]. This lack of knowledge regarding screening can be credited to several factors such as the low educational status of developing countries, little information communicated by the healthcare workers, and the insufficient knowledge of preventive measures amongst them. Other screening barriers include misconceptions about testing guidelines, the socioeconomic status of low-income families, lack of access to testing facilities, personal reluctance due to embarrassment, and family trends of not getting tested due to cultural taboos. [5]. It is crucial to overcome the aforementioned obstacles in order to ensure early screening and treatment of precancerous lesions in women. —Continue